Synthesis of menthols from citral on Ni/SiO2-Al2O3 catalysts - Trasarti, Andres Fernando (2013)
The one-pot synthesis of menthols from citral was studied on Ni/SiO2-Al2O3 catalysts containing 3.6%, 8.8% and 11.4% Ni. The yield of menthols increased with the amount of Ni up to 94% on Ni(11.4%)/SiO2-Al2O3, reflecting the diminution of byproducts formation via acid-catalyzed reactions. The sample deactivation was studied by performing two consecutive catalytic tests. Results showed that Ni(11.4%)/SiO2-Al2O3 was a stable, active, and highly selective catalyst because it contained the appropriate density and strength of bifunctional acid/Ni(0) active sites to efficiently promote the hydrogenation/isomerization pathway involved in the reaction network while avoiding coke formation.